DEVELOPING USWAH LEARNING MODEL TO STRENGTHEN STUDENT CHARACTER IN MADRASAH - Mila Hasanah; Suraijiah; Misbah; Fadzillah Mohammed Osman; Siti Shalihah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Cultural culturation is the impact of the Revolution Era 4.0 and Society 5.0. This is one of the problems in strengthening the character of Rahmatan lil'Alamin students in Madrasah Ibtidaiyah. The research aims to develop an effective Uswah learning model to strengthen the character of Rahmatan lil'Alamin students in Madrasah Ibtidaiyah. The research design applies a 4D development research model (define, Design, Develop, Disseminate). The subjects of the research were 72 students in grade 4 of Madrasah. The criteria for selecting Madrasah is Madrasah Ibtidaiyah, which is in the process of implementing the Independent Curriculum and Religious Moderation. Research instruments use observation, tests, interviews, and documentation. Data analysis using the Tiagarajan Model. The Uswah Learning Model is relevant and valid when applied to all subjects in Madrasah Ibtidaiyah. 90.20% effectiveness rate to strengthen the character of rahmatan lil 'alamin students in Madrasah Ibtidaiyah, especially aspects: Ta'addub, qudwah, tawassuth, muwathanah. This model can be used as a reference for learning innovation to support the internalization of religious moderation and strengthen the character of Rahmatan lil'Alamine students. However, this Uswah learning model can be applied optimally if competent teachers become role models.